Organisational learning capabilities (OLC) and knowledge performance in academic libraries in Malaysia / Mohd Shamsul Mohd Shoid - Mohd Shoid, Mohd Shamsul (2015)
Organisational learning capabilities (OLC) can be defined as the organisational and managerial characteristics of factors that encourage learning process or facilitate an organisation to learn while knowledge performance can be explained as the ability of individual, group and organisation to understand what they have learned. Various works and research have dealt with the analysis of this construct from different views and perspectives. However, research has shown that there were lack of studies that explored the perceptions and relationships between organisational learning capabilities' (OLC) dimensions and knowledge performance in academic libraries. This study was set out to capture the perceptions of organisational learning capabilities among librarians and knowledge performance in academic libraries in Malaysia. A research survey method using questionnaire was distributed to 240 librarians in selected university libraries in Malaysia which reflected the study objectives. From the feedback, only 186 (78%) of the questionnaires were returned and usable for further analysis. Quantitative approach was adopted for this study. The statistical analyses included descriptive and inferential statistics. Parametric tests were used to analyse the data. For parametric analysis, independent samples Mest, one way analysis of variance (ANOVA), Pearson's correlation of coefficient and multiple regression analyses were used. From the findings, the OLC's dimensions on information communication and technology (ICT) was ranked as the highest (mean = 5.65) indicating that it was the most preferred response as perceived by the respondents. Using ANOVA test, the results showed that there were significant differences on shared vision and mission, systems thinking, organisational culture and leadership among respondents with different years of working experience. In terms of work department, the results showed that there were significant differences on transfer of knowledge, organisational culture, leadership and ICT among respective respondents. Results of the findings also revealed that there were significant positive relationship between OLC dimensions and knowledge performance in academic libraries which scored moderately correlated. From multiple regression analysis using stepwise method, dimensions on employees9 skills and competencies, information communication technology, shared vision and mission and transfer of knowledge were found to be the most significant predictor of knowledge performance. Meanwhile, the dimensions on organisational culture, systems thinking, leadership and teamwork cooperation were not significant in predicting the knowledge performance as they were excluded from the model. The outcome of the study is expected to assist the librarians and academic libraries for improving the skills of acquiring knowledge and learning capabilities towards enhancing the knowledge performance.